Framework to prioritize health outcomes of particulate matter exposure using national claims data - Jihye Heo; Jin Lee; Hwamin Woo; Jihee Nam; Suna Kang; Hyunsoo Kim; Whanhee Lee; Kangmo Ahn; Danbee Kang; Eliseo Guallar; Sung Won Kang; Juhee Cho (PLoS ONE, 2025)
Objectives Although particulate matter (PM) exposure poses significant public health risks, previous research has focused on limited clinical areas. However, emerging evidence and pathological mechanisms of PM suggest that PM may exert broader systemic effects across a wide range of diseases. Therefore, we aim to identify and prioritize research questions to evaluate health impacts of PM exposure across various clinical specialties. Methods A structured collaborative process was conducted between April and November 2024 in South Korea, incorporating systematic literature reviews, multidisciplinary expert discussions, and knowledge-sharing seminars. The primary outcomes were the identification of diseases potentially influenced by PM exposure and the development of corresponding research questions. The literature review synthesized more than 417 publications, including the U.S. Environmental Protection Agency’s integrated science assessment materials, a government-issued abstract compendium on PM covering 2010–2019, and studies published from 2020 to 2024 identified via a structured search. These were categorized by exposure duration (short- or long-term) and diseases outcome (incidence or progression). Prioritization was based on three criteria: pathological causality, clinical impact (public health burden), and feasibility using the Korea National Health Insurance Service (K-NHIS). Results A total of 99 experts from epidemiology, data science, and 14 clinical specialties participated. The experts panel (mean age: 46.1 years; mean professional experience: 20.5 years) identified 211 research questions across 80 diseases. These were classified by disease outcome: disease incidence (short-term, 54; long-term, 64) and progression (short-term, 47; long-term, 46). Notably, several clinical areas such as ophthalmology, dermatology, and otolaryngology were underrepresented. Conclusion This structured, multidisciplinary approach broadened the scope of PM-related clinical research beyond commonly studied clinical area. This scalable framework can be adapted in other regions with similar claims data systems to guide evidence-based research agendas and inform public health policies.